2015
DOI: 10.1007/s10854-015-2769-x
|View full text |Cite
|
Sign up to set email alerts
|

The visible light catalytic properties of carbon quantum dots/ZnO nanoflowers composites

Abstract: Carbon quantum dots (C QDs)/ZnO nanoflowers composites were prepared via a simple technical route through which ZnO nanoflowers were prepared by electrospinning-hydrothermal synthesis and dispersed in C QDs solution, then dried at 80°C. The results indicated that ZnO nanoflowers were well combined with C QDs. The visible light photocatalytic activity of C QDs/ZnO nanoflowers coposite was investigated by degradation of Rhodamine B under visible light irradiation, and it is demonstrated that the photocatalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Among all the composites of CQD-decorated multi-shelled ZnO, the obtained ZnO composites exhibit highest photocatalytic activity when the amount of the CQD solution is controlled at 2 g. The reason for this may be that the CQD/ZnO composite can improve the light utilization through its unique up-conversion characteristics; 35 however, the photocatalytic activity of the carbon quantum dots is weaker than that of ZnO. Thus, the higher the content of the carbon quantum dots decorated on the ZnO shells, the more the competition between the light absorption capacities of ZnO and carbon quantum dots; this will lead to a decline in the photocatalytic activity; 36 to study the photocatalytic activity of ZnO decorated with different kinds of carbon quantum dots, we have selected the same decoration ratio (the amount of CQDs in all the adsorption CQD solutions is controlled at 2 g) as a standard to formulate the C T / C 0 -time and ln(C 0 /C T )-time graphs, as shown in Fig. 7.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the composites of CQD-decorated multi-shelled ZnO, the obtained ZnO composites exhibit highest photocatalytic activity when the amount of the CQD solution is controlled at 2 g. The reason for this may be that the CQD/ZnO composite can improve the light utilization through its unique up-conversion characteristics; 35 however, the photocatalytic activity of the carbon quantum dots is weaker than that of ZnO. Thus, the higher the content of the carbon quantum dots decorated on the ZnO shells, the more the competition between the light absorption capacities of ZnO and carbon quantum dots; this will lead to a decline in the photocatalytic activity; 36 to study the photocatalytic activity of ZnO decorated with different kinds of carbon quantum dots, we have selected the same decoration ratio (the amount of CQDs in all the adsorption CQD solutions is controlled at 2 g) as a standard to formulate the C T / C 0 -time and ln(C 0 /C T )-time graphs, as shown in Fig. 7.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…7b exhibits the linear tting line of the curve of ln(C 0 / C T ) versus time, where the slope represents the photocatalytic reaction rate constant. 36 Table 1 lists the reaction kinetics equation and the corresponding parameters of the photocatalytic degradation of MB for the as-prepared photocatalysts. The apparent reaction rate constants (k) are 0.0353, 0.0424, 0.0417, 0.0439, and 0.0725 min À1 for pure ZnO, 2 g-CQD/ZnO, 2 g-NCQD/ZnO, 2 g-PCQD/ZnO, and 2 g-NPCQD/ZnO, respectively.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“… 13 15 . There are some fascinating properties such as chemical inertness, lack of blinking, low toxicity 16 18 , and excellent biocompatibility relative to traditional organic dyes and inorganic semiconductor quantum dots 19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, enhanced photocatalytic degradation against various organic dyes under different light irradiations using different ions doped ZnO and TiO 2 nano/microstructures has been reported [12][13][14][15][16]. Zhang et al [17] have reported the visible light catalytic properties of carbon quantum dots/ZnO nanoflowers composites, and found that the enhanced photocatalytic properties with respect to the carbon quantum dots and also Khataee et al [18] have reported the sonocatalytic degradation of a textile dye over Gd-doped ZnO nanoparticles and their results revealed that the Gd-doped ZnO nanoparticles can be used as a promising catalyst for degradation of organic pollutants with great reusability potential. There are very few attempts have been made for the degradation of organic dyes using Sm 3?…”
Section: Introductionmentioning
confidence: 99%